A primate model for the origin of flake technology. Issue 171 (October 2022) - Luncz, Lydia V.; Arroyo, Adrián; Falótico, Tiago; Quinn, Patrick; Proffitt, Tomos
Abstract: When and how human ancestors first used tools remains unknown, despite intense research into the origins of technology. It has been hypothesized that the evolutionary roots of stone flake technology has its origin in percussive behavior. Before intentional stone flaking, hominins potentially engaged in various percussive behaviors resulting in accidental flake detachments. We refer to this scenario as the 'by-product hypothesis.' In this scenario, repeated detachments of sharp stone fragments eventually resulted in intentional flake production. Here, we tested the circumstances of accidental flake production as a by-product of percussive foraging in wild capuchin monkeys ( Sapajus libidinosus ) from Brazil, the only nonhuman primate known to habitually produce sharp-edged flakes through a percussive behavior. We conducted field experiments where we tested the potential for accidental flake production during nut cracking. We provided three different types of stone with varied material properties as anvils to assess the circumstances in which accidental production of sharp-edged flakes occurs during nut cracking. A further freehand knapping experiment, with the raw material that exhibited accidental flake detachments, allows a direct comparison of flakes that have been intentionally produced by an experienced knapper and flakes produced during nut cracking by capuchin monkeys. Our results show that raw material quality and morphology significantly affect the rate of sharp-edged flake production as well as the resulting lithic signature of this behavior. In addition, accidental flakes produced during capuchin nut cracking on highly isotropic raw material are similar in many respects to intentionally produced flakes by a human knapper. Our field experiments highlight the fact that nut-cracking behavior can lead to the unintentional production of substantial quantities of sharp-edged flakes and therefore supports the 'by-product hypothesis' as a potential mechanism for the emergence of hominin flake technology.